2002
DOI: 10.1103/physrevlett.88.095006
|View full text |Cite
|
Sign up to set email alerts
|

Instability-Triggered Phase Transition to a Dusty-Plasma Condensate

Abstract: Highly charged dust grains in plasma discharges reside at the sheath edge, where the ions stream toward the electrode at speed approximately c(s). Above a critical pressure P(crit), the grains lose their kinetic energy and reach a strongly coupled crystalline state, but for P P(crit) by the combined effect of ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
92
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 20 publications
10
92
0
Order By: Relevance
“…A more comprehensive approach to explain anomalous heating caused by the wake field is described by Joyce and Ganguli et al [7,8,9]. They consider the dynamically shielded potential as described in section 3.2.1 (equation (3.23)), that is obtained by applying linear response theory.…”
Section: Melting and Condensation Transitions Of The Dust Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…A more comprehensive approach to explain anomalous heating caused by the wake field is described by Joyce and Ganguli et al [7,8,9]. They consider the dynamically shielded potential as described in section 3.2.1 (equation (3.23)), that is obtained by applying linear response theory.…”
Section: Melting and Condensation Transitions Of The Dust Systemmentioning
confidence: 99%
“…The observations on phase transitions will be compared to the predictions of theory, in particular to the theoretical description and simulations by Joyce and Ganguli et al [7,8,9]. This work is organized as follows: Chapter 2 gives an introduction into the DLS theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the reason for the large dust kinetic temperature is not definitively known, theories for dust heating have been proposed, including dust heating by wave-particle interactions (e.g. Schweigert et al 1996;Joyce et al 2002). In addition, numerical particle-in-cell (PIC) simulations have shown that dust can get heated by waves in the nonlinear development of the ion-dust streaming instability Winske & Rosenberg 1998;Winske 2004;Fu & Scales 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rosenberg 1993) or, more generally, an ion-dust streaming instability, which also includes the case when the ion flow is superthermal (e.g. Rosenberg 1996;Joyce, Lampe & Ganguli 2002).…”
Section: Introductionmentioning
confidence: 99%